How Does Digital Quiz Motivate Students in EFL Setting? - Aulia, Hilda; Rafi, Muhammad Arif; Permatasari, Regina Putri; Jaufillaili, Jaufillaili; Apandi, Apandi (International Journal of Linguistics and Translation Studies, 2025)
This study examines the effect of digital quizzes, specifically Kahoot, on the motivation for English learning among EFL students at a high school in Indonesia. Motivation is a crucial determinant in learning English, especially in Indonesia, because a lot of students are rarely exposed to English outside the classroom, affecting student engagement and learning results. This research employs a qualitative approach to investigate the impact of Kahoot on students' enthusiasm, participation, and confidence in learning English. Data were gathered via classroom observations of 35 students and semi-structured interviews with six students, and for data analysis, we use thematic analysis. The results indicate that Kahoot markedly increases student motivation by rendering learning more interactive and enjoyable. The majority of students indicated heightened engagement, enthusiasm, and diminished anxiety while utilising the platform. The research underscores the efficacy of gamification in language acquisition and offers guidance for educators aiming to develop more dynamic and engaging learning environments.